The Teilhard de Chardin unpublished letters to Édouard Le Roy:approach for understanding the conflict between Science, Philosophy and Theology - Sequeiros, Leandro; Medina Casado, Manuel; Medina de la Fuente, María José; Euvé, François (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The readers of Teilhard de Chardin’s works have known the correspondence with Édouard Le Roy, as friend, confident and professor-pupil. Today the contribution of Le Roy to Teilhard synthesis and what Teilhard enriched the free creativity of Le Roy by Teilhard is not well studied. But an intellectual symbiosis was created between themselves; into the conversations and letters we can perceive the complicity and a surprising convergence of orientations. Nevertheless, the spanish reader has not access to the Teilhard letters remitted to Le Roy, but these have been frequently related. We present here a perspective of the letters, published in France in 2008, by the jesuit François Euvé, professor of Theology in the Faculties of the Society of Jesus in Paris. We hope to see the spanish translation of the letters soon, as a cooperation to historical rehabilitation, into the present ecclessial and theological contexts, related to the clarificated and exciting thought of Pierre Teilhard de Chardin.
Keywords: Teilhard de Chardin; Édouard Le Roy; Evolution; Dogma; Theology; Anthropology; Paleontology; Philosophy of Biology